# Laplace Transform

1. Jun 10, 2012

### p75213

1. The problem statement, all variables and given/known data
Is there an easier way of solving this rather than doing the integral?
Find the laplace transform of:

$$t{e^{ - t}}u(t - 1)$$

2. Relevant equations

3. The attempt at a solution
$$\int_1^\infty {t{e^{ - t}}} {e^{ - st}}dt = \int_1^\infty {t{e^{ - t(1 + s)}}} dt = \frac{{{e^{ - (s + 1)}}}}{{{{(1 + s)}^2}}} + \frac{{{e^{ - (s + 1)}}}}{{1 + s}}$$
1. The problem statement, all variables and given/known data

2. Relevant equations

3. The attempt at a solution

2. Jun 10, 2012

### LCKurtz

That integral isn't that tough, but if you prefer, you can use some of the theorems. For example, you have, if $\mathcal L(f(t)) = F(s)$ then $\mathcal L(tf(t))=-F'(s)$. Also, $\mathcal L(e^{at}f(t) = F(s-a)$ and $\mathcal L(u(t-1))=\frac{e^{-s}}{s}$.

So starting with $\mathcal L(u(t-1))=\frac{e^{-s}}{s}= F(s)$, then $\mathcal Le^{-t}u(t-1)=F(s+1) =\frac{e^{-(s+1)}}{s+1}$ and $$L(te^{-t}u(t-1)) = -\frac d {ds}\left(\frac{e^{-(s+1)}}{s+1}\right)=\frac{e^{-s+1}(s+1)+e^{-s+1}}{(s+1)^2}$$which is the same answer.

3. Jun 10, 2012

### p75213

True - it isn't that tough. But I am not so keen on integration by parts if I can avoid it.